HUBUNGAN PENGETAHUAN ANAK USIA SEKOLAH TENTANG PENCEGAHAN KARIES GIGI DENGAN TERJADINYA KARIES GIGI - Novia Andini; Ganis Indriati; Febriana Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Dental carries is a major oral health problem in most countries, affecting majority of schoolchildren. Children in the 6 – 12 year age can be at great risk from dental carries. This could be attributed to poor knowledge and awareness towards oral health.The study was done to find out the correlation between school children level of knowledge regarding prevention and occurrence of dental carries at Payung Sekaki Pekanbaru Public Health Center. A crosssectional correlation research design was used for this study. The subjects consisted of 78 schoolchildren who were selected using purposive sampling method. Structured questionnaire and observation sheet that has been tested for validity were used to collect the data. The results showed that 97.4% of the schoolchildren (76 respondents) had good knowledge regarding the prevention of dental carries, while 60 respondents (76.9%) had the incidence of dental carries. Statistical analysis with Chi-Square test indicated that there was no correlation between school-age knowledge about the prevention of dental carries and the occurrence of dental carries with a p value of 1,000 (> 0.05). Hence, this study may recommend to health workers to promote dental health programs in schools.   Keywords: dental carries, knowledge, prevention, school age